2002
DOI: 10.1103/physrevlett.89.282501
|View full text |Cite
|
Sign up to set email alerts
|

Octupole Vibration in SuperdeformedD66152y86

Abstract: Nine transitions of dipole character have been identified linking an excited superdeformed (SD) band in 152Dy to the yrast SD band. As a result, the excitation energy of the lowest level in the excited SD band has been measured to be 14 238 keV. This corresponds to a 1.3 MeV excitation above the SD ground state. The levels in this band have tentatively been determined to be of negative parity and odd spin. The measured properties are consistent with an interpretation in terms of a rotational band built on a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…It shows a rather constant excitation routhians in a wide range of ω rot = 0 ∼ 0.7 MeV. Later in 2002, its octupole character has been confirmed by the measurement of the interband transitions and the spin identification [62,63]. The ω rot -dependence of the routhian well agrees with the theoretical prediction.…”
Section: Octupole Vibrations Withsupporting
confidence: 72%
“…It shows a rather constant excitation routhians in a wide range of ω rot = 0 ∼ 0.7 MeV. Later in 2002, its octupole character has been confirmed by the measurement of the interband transitions and the spin identification [62,63]. The ω rot -dependence of the routhian well agrees with the theoretical prediction.…”
Section: Octupole Vibrations Withsupporting
confidence: 72%
“…In fact, various mean-field calculations [7][8][9] and quasiparticle random phase approximation (RPA) [10,11] on the basis of the rotating mean field (cranked shell model) indicated that SD nuclei are very soft against both the axial and nonaxial octupole deformations. Thus, low-frequency octupole vibrations have been predicted to appear near the SD yrast lines [12], and recently discovered in experiments for heavy SD nuclei in the Hg-Pb region [13], and also in 152 Dy [14].…”
Section: Introductionmentioning
confidence: 79%
“…Two years later an experiment using the same beam and target but now with TESSA3 revealed the main discrete band [33] associated with the ridge structure as shown in figure 5. Further experiments both at Daresbury Laboratory and elsewhere have revealed a rich spectroscopic world in the superdeformed minimum of 152 Dy, see [35,[41][42][43][44] and references therein. included, this pattern is diluted but a fairly regular scheme of gaps still persists.…”
Section: The Discovery Of High-spin Nuclear Superdeformation and Iden...mentioning
confidence: 99%